The use of creative problem solving model to develop students’ adaptive reasoning ability: Inductive, deductive, and intuitive - Bansu Irianto Ansari; Taufiq Taufiq; Saminan Saminan (Universitas Islam Negeri Maulana Malik Ibrahim, 2020)
This study was aimed at investigating adaptive reasoning ability of junior high school students through the implementation of the creative problem solving model. This study employed a mixed-method approach using an embedded concurrent strategy. Thirty students were selected randomly as the sample from 180 Year 8 students, and six students were selected to be observed and further interviewed after the final test. The instruments used were a test and interview questions. The results showed that there was a significant increase in the students' ability between the pre-test and post-test. In addition, there was also an increase in the ability of the six students based on an adaptive reasoning rubric. The increase was more dominant for the first and fifth indicators while the increases of the second and fourth indicators varied. Some students were able to solve the problem based on the indicators, but it was incomplete due to miscalculation, and some students were lacking in the ability to find the pattern and drawing a correct conclusion as a result of the profound basic knowledge. In general, these results indicated that students were able to develop adaptive reasoning although the maximum score could not be achieved.The use of creative problem solving model to develop adaptive reasoning ability: Inductive, deductive and intuitive